Taxonomy and DNA barcoding of the dark-winged fungus gnat genus Zygoneura Meigen (Diptera: Sciaridae) from China, with revision of the type materials - Shah, Bismillah; Shao, Yisa; Du, Hong; Wang, Yang; Huang, Junhao (Zootaxa, 2024)
The genus Zygoneura Meigen is revised thoroughly from China, and 14 species are recognized and illustrated, including four new species: Zygoneura (Allozygoneura) xizangensis Shah & Huang sp. nov., Zygoneura (Pharetratula) minuscula sp. nov., Zygoneura (Pharetratula) motuoensis sp. nov. and Zygoneura (Pharetratula) yangi sp. nov. In addition, Zygoneura (Pharetratula) divergens (Mamaev), Zygoneura (Pharetratula) flavicornis (Mamaev), and Zygoneura (Pharetratula) subdivergens (Mohrig & Mamaev) are reported for the first time from China. The identification of these species is supported by both morphological characteristics and sequence data obtained from cytochrome oxidase subunit one (COI) in the DNA barcode analysis. Furthermore, a checklist of the known Zygoneura species in China is also provided, along with an identification key for males.